Productivity spillovers from FDI: Ownership structures, domestic firm characteristics, and FDI characteristics - Jannick Damgaard (Danmarks Nationalbank, 2011)
This paper is unique in testing the importance of the foreign ownership definition when estimating productivity spillovers from foreign direct investment (FDI) to domestic firms; a crucial aspect in countries with a widespread use of holding companies. In addition, it moves beyond the standard framework by not only analyzing aggregate productivity spillovers, but also testing the importance of both domestic firm characteristics and FDI characteristics. The empirical analysis is the first one to exploit the rich details offered by official Danish firm-level panel data. The analysis displays significant evidence of negative spillovers at the aggregate level, but the results differ widely across industries. It also reveals that not including firms under indirect foreign control in the group of foreign firms, as is done in some studies, leads to biased results. With regard to domestic firm characteristics, high export orientation and high competition mitigate some of the negative productivity spillovers. Finally, the estimations show that the negative spillovers largely stem from foreign firms (i) with low productivity, (ii) with high foreign trade orientation, and (iii) ultimately controlled by investors outside Scandinavia.
Keywords: D24; F21; F23; O33; 330; productivity; spillovers; FDI; determinants; Direktinvestition; Produktivität; Spillover-Effekt; Wettbewerb; Nordeuropa